Development and Validation of the Companion's Satisfaction Questionnaire of Patient's Hospitalized in Intensive Care Units - Dehghani, Ali (Investigación y Educación en Enfermería, 2024)
Objective. The current study aimed to develop and validate of companions’ satisfaction questionnaire of patients hospitalized in ICUs. Methods. This is a methodological study that was performed in three phases: In the first phase, the concept of companion's satisfaction of patients hospitalized in ICUs was defined through qualitative content analysis method. In the second phase, early items of questionnaire were generated based on findings of the first phase. In the third and final phase, validation of the questionnaire was evaluated using face, content and construct validity as well as reliability. Results. In exploratory factor analysis, three subscales including: satisfaction with nursing staff communication (5 items), satisfaction with nursing care (12 items), and satisfaction with decision making (5 items) were extracted by Eigen value above one and factor load above 0.5. Internal consistency and stability of the developed questionnaire confirmed with 0.94 and 0.95 respectively that indicated acceptable reliability. Conclusion. The 22-item developed questionnaire is valid and reliable for measurement of levels of companion's satisfaction of Iranian patients hospitalized in ICUs.